A Public Policy on Education for the Realization of Global Citizenship and Human Rights: A Possibility for the Restorative Inclusion of Human Dignity - Morales Carrero, Jesús Alfredo (2025)
The multidimensional transformation of society as a global task of the universal educational and political agendas constitutes the hopeful possibility of building a better world driven by the common commitment to unify efforts around a dignified conviviality. This research, as a result of a documentary review, proposes a public policy on education with emphasis on the realization of global citizenship and human rights. It presents both dimensions and strategies designed to integrate sustainable and transcendental human dignity, conceived as the widespread aspiration underlying the construction of a conscious society. This society is envisioned as supportive of multiple belongings, open to diversity and pluralism, and committed to a collective vocation that, through ethical and moral attitudinal repertoire, leads to the revitalization of the social fabric. In conclusion, confronting individualism, fundamentalisms that sustain extreme positions, and intolerant attitudes, requires synergistic and strategic institutional efforts focused on enhancing critical thinking and the reciprocal commitment to safeguard personal autonomy, both individual and collective performance, as well as socially inclusive treatment. These requirements are inherent to the expansion of the possibilities to achieve both fraternal and supportive encounters and reconciliation that society in general demands to function coherently.